The search for point-like neutrino sources with ANTARES and KM3NeT-ARCA telescopes - Zavatarelli Sandra; Alves Garre Sergio; Aublin Julien; Caiffi Barbara; Heijboer Aart; Illuminati Giulia; Kulikovskij Vladimir; Muller Rasa; Parisi Vittorio; Sanguineti Matteo; van Eeden Thjis (EPJ Web of Conferences)
The multi-messenger approach has recently paved the way for possible breakthroughs in our comprehension of high energy particle emission in the Universe. Neutrino telescopes are essential for highlighting the hadronic component of these phenomena, in addition to testing possible correlation with known sources of gamma rays. Joint analyses of data from complementary facilities may provide enhanced sensitivity. This contribution explores the sensitivity as a function of the source declination for a combined analysis of data collected by two neutrino telescopes located in the depths of the Mediterranean Sea, ANTARES and KM3NeT/ARCA. A catalogue of approximately one hundred point-like and extended sources is presently investigated for neutrino emissions: the list encompasses bright γ-ray emitters, galactic γ-ray sources, extragalactic sources as radio-loud AGNs and the most significant candidate sources studied by IceCube.